Operation and experiences of the second generation of the Schengen evaluation system - Lénárd Zsákai (Belügyi Szemle, 2025)
Aim: This study aims to explore and summarise nearly a decade of the operations of the second-generation Schengen evaluations, along with the direct experiences related to its implementation.